1975
DOI: 10.1002/pol.1975.170131201
|View full text |Cite
|
Sign up to set email alerts
|

Formation of free radicals in photoirradiated cellulose. VI. Effect of lignin

Abstract: The effect of lignin on free‐radical formation in photoirradiated pulp was studied by means of electron spin resonance spectroscopy. Samples were irradiated with light of wavelength longer than 3400 Å as well as longer than 2537 Å. Radical formation in aspen lignin was observed before and after irradiation with light of wavelength longer than 3400 Å. Upon irradiation, free radicals were formed in a pulp sample with 0% lignin content only when oxygen was present. On irradiation with light longer than 2537 Å, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…Studies of wood photodegradation suggest that the photon energy absorbed by cellulose in the UV range is likely to delocalize and transfer to lignin, causing degradation of the latter (27). The presence of lignin is therefore actually predicted to protect cellulose from photodegradation, a phenomenon that has been documented to some extent and attributed to the strong light absorption of lignin and its high capacity for autoxidation (27,32). Our results support the idea that lignin was the primary loss product due to photodegradation in our standard substrates, and they are consistent with observations indicating the disappearance of lignin in litter exposed to high natural UV-B radiation (20) and increased biotic lability of plant litter after solar radiation exposure (21,26).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of wood photodegradation suggest that the photon energy absorbed by cellulose in the UV range is likely to delocalize and transfer to lignin, causing degradation of the latter (27). The presence of lignin is therefore actually predicted to protect cellulose from photodegradation, a phenomenon that has been documented to some extent and attributed to the strong light absorption of lignin and its high capacity for autoxidation (27,32). Our results support the idea that lignin was the primary loss product due to photodegradation in our standard substrates, and they are consistent with observations indicating the disappearance of lignin in litter exposed to high natural UV-B radiation (20) and increased biotic lability of plant litter after solar radiation exposure (21,26).…”
Section: Resultsmentioning
confidence: 99%
“…É conhecido que o cerne concentra maior quantidade de extrativos (Kollmann e Côté, 1968). Vários autores (Hon, 1975); Desh e Dinwoodie (1993) relatam que a definição da cor na madeira é fortemente influenciada pela quantidade de extrativos presentes no cerne, onde os componentes fenólicos desempenham importante papel (Scalbert et al, 1987;Janin et al, 1990a). Quanto à lignina, observando-se a Tabela 1, nota-se que as médias de lignina total, lignina solúvel e lignina insolúvel são diferentes entre os clones, mas não variam entre as duas posições longitudinais estudadas.…”
Section: Resultados E Discussõesunclassified
“…We also took into account results from previous extensive ESR studies of cellobiose, cellulose, and other disaccharides (Kawano and Logarezzi 1995;Kuzuya and Yamauchi 1998;Ershov 1998;Wach et al 2004;Mohanty and Singh 1988;Wach et al 2003;Hon 1975;Ershov and Isakova 1984;Yamauchi et al 1999;Kuzina et al 2004;Engalytcheff et al 2004;Kuzuya et al 1999;Ershov et al 1977). The X-band ESR spectra were typical of radicals in saccharides with a relatively low total radical concentration (approx.…”
Section: Radical Identification and Esr Parametersmentioning
confidence: 99%
“…Abstraction of H-atom at C 1 position can, moreover, induce cleavage of the glucosidic link with formation of an alkoxy RO Á radical giving a singlet ESR line. Intermediate transient radical centres have also been observed, as hydrogen atoms (doublet with 50.8 mT splitting) (Hon 1975), formyl radicals (doublet with 12.9 mT splitting) (Hon 1975), and O Á H and other oxygen-centred radicals. It has been also reported that after cleavage of glucosidic bonds at low temperatures the two radicals appear on the pyranose rings and are converted to allylic radicals on heating (Ershov and Isakova 1984).…”
Section: Introductionmentioning
confidence: 95%